Resealed Erythrocyte Drug Delivery System - Sharma, Purshottam; Khinchi, M. P.; Dubey, Chetan Kumar; Shama, Parveen (Asian Journal of Pharmaceutical Research and Development, 2017)
Erythrocytes, the most abundant cells in the human body, have potential carrier capabilities for the delivery of drugs. New drug delivery systems have been developed to overcome the limitations associated with the conventional drug delivery systems in order to improve the patient compliance and safety. They can be classified based on their size as (i) microcarriers for example, Liposomes, resealed, microspheres (ii) nanocarriers for example, niosomes, pharmacosome, aquasomes, solid lipid nanoparticles (SLN) (iii) variable carriers for example, dendrimers. Controlled Release drug delivery is one which delivers the drug at a predetermined rate, for locally or systemically, for a specified period of time. Patient comfort and compliance, Reduction in Health care cost, Patient variation are the advantages of controlled release drug delivery Systems, disadvantage are dumping, In-vitro In-vivo correlation, Increased potential for first pass effect. We are discusses mechanism of drug release such as- Immediate, modified, delayed & extended release. Red blood cells are the most common type of blood cells and the vertebrate organism's. Red blood cells (RBCs) have shapes like biconcave discs with a diameter of 7.8μm and thickness near 2.2μm. The several methods are present in this article Hypotonic Heamolysis, Hypotonic dilution, Isotonic Osmotic. various characterization parameters are discusses example- Shape & surface of morphology, Drug content, drug release. applications of resealed erythrocytes- In-vivo, Slow Drug Release, Drug targeting.